Effect of Azolla filiculoides Application on Weed Population in Paddy Fields - Sivaneson, S.; Ponnegippenthiraraja, A. (University of Jaffna, 2019)
The integrated use of organic and inorganic fertilizers is desirable to sustain paddy cultivation. Study was conducted at Rice Research Station, Paranthan, Sri Lanka to develop effective weed control method to gain economic return from irrigated paddy fields in the Dry Zone. The experiment was carried out during the period of November-February, 2017 (Maha), using randomized complete design with six treatments with three replicates; Azolla only, Azolla with three nitrogen levels (25%, 50%, 100% kg N/ha) of the recommended level of nitrogen, only recommended level of nitrogen (100 kg N/ha) and plot with absence of chemical fertilizer and Azolla (control). The nutrients potassium and phosphorus were applied to respective plots based on the recommended level. Results showed partial suppression of weed growth by Azolla filiculoides even under full plot area coverage. The range of weed suppression at rice 30 days after planting was 64.21 – 88.31%. However, Azolla failed to suppress the growth of some weeds such as Aeschynomene indica, Ipomoea aquatic and Cyperus iria. Plots with combined application of Azolla and different levels of nitrogen fertilizer revealed greater value for weed control efficiency the range of 76.81 – 80.93%. There was no significant difference in the yield in plots treated with Azolla + recommended level of N fertilizer, Azolla + 50 kg/ha recommended level of N fertilizer (6066 and 5966 kg/ha respectively) and only recommended level of N fertilizer without Azolla (5533 kg/ha). Therefore the use of Azolla in the rice cultivation has greater influence on suppressing the weeds and also reduces the nitrogen fertilizer and herbicides application requirements.
Keywords: Azolla; Fertilizer; Nitrogen; Suppress; Weeds